1994
DOI: 10.1002/app.1994.070541113
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ABS type on morphology and mechanical properties of PC/ABS blends

Abstract: Texas 7871 2 SYNOPSISThe morphology and the mechanical properties of polycarbonate (PC) blends with different acrylonitrile-butadiene-styrene (ABS) materials were investigated. PC/ABS blends based on a mass-made ABS with 16% rubber and large (0.5-1 pm) rubber particles are compared to blends based on an emulsion-made ABS with 50% rubber and small, monodisperse (0.12 pm) rubber particles over the full range of blend compositions. The blends with the bulk ABS showed excellent impact strength for most composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 37 publications
3
61
0
1
Order By: Relevance
“…Experimental results showed that the averaged impact fracture energies of the wider and thinner specimens were 112 J/m and 918 J/m, respectively. Lombardo et al [11] studied 3.18 mm thick samples with sharp and standard notch. The sample with sharp notch had 80 J/m fracture energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results showed that the averaged impact fracture energies of the wider and thinner specimens were 112 J/m and 918 J/m, respectively. Lombardo et al [11] studied 3.18 mm thick samples with sharp and standard notch. The sample with sharp notch had 80 J/m fracture energy.…”
Section: Introductionmentioning
confidence: 99%
“…The impact response of PC has been extensively studied in the literature by experimental research works, ranging from high velocity impacts [4][5][6][7][8][9] by means of gas gun impact tests to low velocity impacts [1,2,10,11], and by means of falling weight tests or Izod impact tests. Shah [4,5] carried out low velocity single and multiple impact tests on a thin PC armor plate.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al 5 have demonstrated the toughening of PC/ABS blends with higher rubber content in the ABS component, at the cost of increased melt viscosity. Lombardo et al 6 have reported that small rubber particles e †ectively toughen the PC. Increase in the molecular weight of PC increases the melt viscosity and ductility of PC/ABS blends.…”
Section: Introductionmentioning
confidence: 99%
“…The filler generated similar contrast as ABS or MBS and hence it is not very difficult to clearly separate the filler component from ABS or MBS. The ABS morphology in PC matrix has been studied earlier [13] and the mechanical strength of the PC/ABS polymer blend was compared with morphology and dispersion of ABS in PC matrix. Similarly, MBS dispersion in PC matrix has also been investigated by CTEM [14].…”
Section: Resultsmentioning
confidence: 99%